دور الاتصالات التسويقية المتكاملة في تقديم وتسويق الخدمات المصرفية: دراسـة تطبيقية على فروع المصارف التجارية بمدينة الزاوية - عبد الكريم ساسي النسر; عبدالسلام العزومي عبدالسلام (Surman Journal of Science and Technology, 2025)
This study aimed to identify the role of integrated marketing communications in providing and marketing banking services. The field study was conducted on commercial bank branches in the city of Zawiya. To achieve the study objectives, the descriptive analytical approach was used, and a questionnaire was used to collect all data and information, analyze them, and interpret them using the (SPSS) program, which contains a package of statistical tests. The study reached the most important results, the most important of which is that integrated marketing communications methods can contribute positively to enhancing the effectiveness of providing and marketing banking services. There is also an urgent need to use integrated marketing communications methods in marketing banking services effectively to ensure access to all customers and influence them better. A set of recommendations was presented, most notably that the bank management should develop a marketing communications strategy for its ability to enhance awareness among bank customers and attract more new customers. Also, relying on the use of new technological techniques such as electronic marketing and social media facilitates the process of reaching and interacting with customers, and expanding the scope of marketing for banking services to target diverse categories of customers by understanding their needs and providing integrated marketing offers.